The use of an integrative approach to improve accuracy of species identification and detection of new species in studies of stream fish diversity - Pereira, Luiz Henrique Garcia; Castro, Jerson Rogelio Chanchay; Vargas, Pilar Mireya Huatatoca; Gomez, Jose Alejandro Morales; Oliveira, Claudio [UNESP] (Springer Nature, 2021)
In this study, we made an inventory of the stream and headwater ichthyofauna of the left bank of the Itaipu Dam Reservoir, located in the lower part of the Upper Paraná River basin, using an integrative approach of molecular and morphological data. The area is located in the western portion of the Paraná state in Brazil, in an area of about 8,000 km2 highly impacted by deforestation and intensive agriculture. For taxonomic identification of species, we used an identification key combined with the DNA barcoding approach. We found 48 species belonging to six orders, 13 families, and 37 genera. The Siluriformes and Characiformes were the most representative orders (75%) and the Characidae was the most representative family (20.8%). Nine species prevailed in this region, making up to 86% of all specimens collected. The integrative approach proved to be useful by allowing the unambiguous identification of all species, including those cases in which morphological characters were not conclusive for species identification, cases of cryptic species, and species with high morphological plasticity. In addition, the integrative approach highlighted six to 13 new putative species depending on the approach considered. Our study provides a relevant contribution to the knowledge of fish diversity in a poorly studied area of the Paraná River basin. We showed that the use of an integrative approach in inventory studies improves species identification and the discovery of new, cryptic, and overlooked species, being a powerful and necessary tool to quantify biodiversity.
Keywords: Checklist; Conservation; DNA barcoding; Fish distribution; Fishes; Paraná River basin